Quaternized chitosan nanoparticles loaded with the combined attenuated live vaccine against Newcastle disease and infectious bronchitis elicit immune response in chicken after intranasal administration - Kai Zhao; Shanshan Li; Wei Li; Lu Yu; Xutong Duan; Jinyu Han; Xiaohua Wang; Zheng Jin (Taylor & Francis Group, 2017)
Newcastle disease (ND) and infectious bronchitis (IB) are important diseases, which cause respiratory diseases in chickens, resulting in severely economic losses in the poultry industry. In this study, N-2-hydroxypropyl trimethyl ammonium chloride chitosan (N-2-HACC) and N,O-carboxymethyl chitosan (CMC) were synthesized as adjuvant and delivery carrier for vaccine antigens. N-2-HACC-CMC/NDV/IBV nanoparticles (NPs) (NDV/La Sota and IBV/H120 encapsulated in N-2-HACC-CMC NPs) and N-2-HACC-CMC/NDV-IBV NPs (the mixing of N-2-HACC-CMC/NDV NPs and N-2-HACC-CMC/IBV NPs in a ratio of 1:1) were prepared by the polyelectrolyte composite method, respectively. Both nanoparticles exhibited lower cytotoxicity and higher stability. Their bioactivities were maintained when they were stored at 37 °C for three weeks. Release assay in vitro showed that both NDV and IBV could be sustainably released from the nanoparticles after an initial burst release. In vivo immunization of chickens showed that N-2-HACC-CMC/NDV/IBV NPs or N-2-HACC-CMC/NDV-IBV NPs intranasally induced higher titers of IgG and IgA antibodies, significantly promoted proliferation of lymphocytes and induced higher levels of interleukine-2 (IL-2), IL-4 and interferon-γ (IFN-γ) than the commercially combined attenuated live vaccine did. This is the first study in the field of animal vaccines demonstrating that intranasal administration of chickens with antigens (NDV and IBV) encapsulated with chitosan derivative could induce humoral, cellular, and mucosal immune responses, which protected chickens from the infection of highly virulent NDV and IBV. This study indicated that N-2-HACC-CMC could be used as an efficient adjuvant and delivery carrier for further development of mucosal vaccines and drugs and could have an immense application potential in medicine.